Mainstreaming Gender in Pursuit of Millennium Development Goals in Water Resource Governance in Buhera, Zimbabwe - Chifamba, Ephraim (International Journal of Social Sciences and Management, 2014)
Women have the primary role for the management of household water supply, sanitation and health. Water is necessary for drinking, but also for food production and preparation, personal hygiene, care of the sick, cleaning, washing and waste disposal. Because of their dependence on water resources, women have accumulated considerable knowledge about water resources, including location, quality and storage methods. However, efforts geared towards improving the management of the finite water resources and extending access to safe drinking water and adequate sanitation, have often overlooked the central role that women play in water management. The study used both qualitative and quantitative research methodologies. The research noted that despite increased gender awareness and the availability of much more information on women’s and men’s roles in water management, gender is not yet mainstreamed into this sector. The study revealed that prospects for effective gender mainstreaming in water resource management will hinge on how the main agenda can address the transformation of gender relations and treat water as a human right so as to realize the Millennium Development Goals (MDGs) in Buhera. A gender equity approach within the water sector, should strive for a more balanced division between women and men in access to information, sharing of contribution, the degree of decision making, access to resources and benefits and the control over water resources. Addressing women’s concerns and mainstreaming gender in water governance through a livelihood approach is critical because this generates an understanding of people’s livelihood strategies and their decision making mechanisms and processes. Significant support and capacity development are required to enhance the participation in decision making processes for the success of water management initiatives. DOI: http://dx.doi.org/10.3126/ijssm.v1i1.8946 Int. J. Soc. Sci. Manage. Vol.1(1) 2014 10-21